Keloid Nodule Metabolic Activity for Continuous Expansion. Issue 8 (24th August 2022) - Ueda, Koichi; Lee, Yuumi; Inomata, Yosuke; Taniguchi, Kohei; Uchiyama, Kazuhisa; Ito, Yuko
Abstract : Background: We previously reported that keloid nodules had such specific structures that higher expression of autophagy proteins and glycolytic markers was observed in the central zone fibroblasts than in marginal zone fibroblasts. The purpose of this study is to investigate how keloid nodules play a role in metabolic activity for continuous expansion. Methods: A total of 57 nodules were randomly chosen from seven keloid samples and divided into four groups of disease duration (2, 4, 6, and 17 years). Immunohistochemical and immunofluorescent analyses were performed. Results: Immunohistochemical analysis with anti-CD-31 confirmed that the nodules had a structure with a greater number of vessels in the marginal zone than in the central zone. The density of fibroblasts in nodules (190.29 ± 64.45) was significantly higher than that of surrounding connective tissue (140.18 ± 63.94) ( P < 0.05). The area of each nodule increased for 2 to 4 years, then decreased, graphically represented by an approximately horizontal line, to 17 years. The ratio of total nodule area/dermis area increased as disease duration lengthened. The maximum ratio was the 17-year group at 48.01%. The nodule number/dermis area ratio rose approximately with advancing disease duration. Conclusions: Instead of increasing the size of the nodules, their number and total area increased within the keloid lesions. We believe that the keloid nodules must play an important role in energy metabolic activity for continuous growth by increasing in number and total area.